The Role of Regional Government in Maintaining Local Traditions and Wisdom in Banyumas - Solehudin, Rd. Heri (Sospol, 2024)
This study aim to explores the role of government in guarding and protecting local wisdom, with studies of cases on the phenomenon of Lengger Banyumas. Lengger Banyumas, again a traditional ritual, has undergone transformation and become recognized as entertainment in a wide variety of ways. The focus of the study is to analyze efforts by the concrete of the government to preserve and protect aspects of wisdom locally contained in Lengger Banyumas. This is a type of study description that is qualitative and descriptive, with an approach to ethnography. This study also involves the analysis of documents related to government policy, interviews with holders of interests, and observations directly related to implementation policy. Research results show that the government's role is significant in guarding and protecting local wisdom through various policies, such as conservation programs, culture promotion, tourism sustainability promotion, and coaching community members. However, challenges like modernization and globalization also gave rise to dilemmas in effort preservation. This Study gives outlook deep about dynamics role government in conserve wisdom local, esp in context Lengger Banyumas. Implications from the study can become the basis. To repair government policies and strategies in support of continuity wisdom local, all at once consider various changing times that can influence existence and values from phenomenon culture.